2019
DOI: 10.1080/15384101.2019.1570655
|View full text |Cite
|
Sign up to set email alerts
|

The cell-cycle transcriptional network generates and transmits a pulse of transcription once each cell cycle

Abstract: Multiple studies have suggested the critical roles of cyclin-dependent kinases (CDKs) as well as a transcription factor (TF) network in generating the robust cell-cycle transcriptional program. However, the precise mechanisms by which these components function together in the gene regulatory network remain unclear. Here we show that the TF network can generate and transmit a "pulse" of transcription independently of CDK oscillations. The premature firing of the transcriptional pulse is prevented by early G1 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 72 publications
(124 reference statements)
0
21
0
Order By: Relevance
“…The regulatory network in Figure 3 is a simplified version of the wavepool model, introduced in [22]. This model has been corroborated experimentally [31,32,33] and describes the mechanism for controlling the cell-cycle transcriptional program.…”
Section: Cell Cycle Data Modelmentioning
confidence: 82%
See 1 more Smart Citation
“…The regulatory network in Figure 3 is a simplified version of the wavepool model, introduced in [22]. This model has been corroborated experimentally [31,32,33] and describes the mechanism for controlling the cell-cycle transcriptional program.…”
Section: Cell Cycle Data Modelmentioning
confidence: 82%
“…This data can be then compared to a partial order computed from the experimental time series data, at different levels of assumed experimental measurement uncertainty ε. We illustrate our approach on data from the yeast cell cycle, where the regulatory network is welldescribed and has substantial experimental validation [22,40,28,41,31,42].…”
Section: Discussionmentioning
confidence: 99%
“…7 ). YOX1 , a TF expressed in mid-G1 through early S phage, interplays with S-specific TF— YHP1 , function as transcriptional repressor to negatively regulate MCM1 - FKH2 - NDD1 -mediated G2/M-G1 transition during cell cycle progression 95 . Recently, a research has reported that ROX1 is in promotion of RAP1 - HAP1 - MSN4 module, which is an important branch for G2/M to G1 phase transition in yeast 96 .…”
Section: Resultsmentioning
confidence: 99%
“…Another study in budding yeast has provocatively demonstrated that, although a large portion of the genome is transcribed cyclically during the cell division cycle, a significant fraction (~70%) of these genes can continue to express periodically even in the absence of a robust cell cycle progression ( Orlando et al, 2008 ). This striking finding has rightly inspired a number of more recent work ( Cho et al, 2019 ; Cho et al, 2017 ; Rahi et al, 2016 ) to validate these findings, and although there does not seem to be a strict consensus, it is somehow clear that the periodic transcription in arrested cells may not be as global as it was originally postulated. Importantly, however, there appear to be some genes that can display periodic expression in the absence of a robust cell cycle oscillator.…”
Section: Molecular Determinants and Roles Of Autonomous Clocksmentioning
confidence: 90%